Barriers to the care of febrile patients in a malaria endemic area. El Bagre (Antioquia, Colombia) 2016 (2020)
ABSTRACT: Abstract Objective: identify constraints of patients with acute febrile syndrome to institutional care services access, emphasizing the identification of communication barriers. Method: this is a descriptive study that involves qualitative research techniques including malaria care service patients as well as assistance and administrative personnel of El Bagre town in Antioquia, Colombia in 2016. Semi-structured individual surveys, interviews and focus groups were used. Results: users listed difficulties including transportation, insufficient number of appointments and absence of personnel to access healthcare. Communication difficulties were related to the information provided in the paperwork and documents filled out to attend healthcare facilities, scarce information about diagnostic, control, and adherence to antimalarial treatment; additionally some patients did not use Spanish to communicate in oral or write form. Conclusion: the creation of health models based on structural transformations that encompass the needs of Healthcare System actors and communities is a must, which allows the establishment of foundations for a multicultural society project.